The theory and empirics of the structural reshaping of globalization - Buckley, Peter J. (Journal of International Business Studies, 2020)
Petricevich and Teece’s (2019) article on the reshaping of globalization raises profound issues on the theory and empirics of international business. The fracture in the world economy between the USA and China is the result of Government policy, but its relationship to rising VUCA (volatility, uncertainty, complexity, and ambiguity) elements in globalization is more complex than simple policy changes. This paper suggests that a reappraisal of theory is required, not least because of the eruption of Covid-19, but that internalization theory is the best source of theoretical restructuring in the face of the new empirical realities facing the global economy.